(untitled) (La U Investiga, 2018)
Tumors of the carotid body or paragangliomas are rare lesions. They can become bilateral. Most are sporadic, family members associated with various genetic syndromes. Compared with the sporadic appearance, family presentation tends to appear at younger ages and to have multiple localization. It is the presentation of 2 cases diagnosed and operated at the modern Ciudad de Ibarra Clinic.